Implementasi Layanan Program Bimbingan Konseling dengan Model Alih Tangan Kasus di SMKN 1 Cijulang - Elsa Dita Fitria; Indah Maulidah; Panisa Dwi Julian; Tiara Dewi Lestari (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
This study aims to determine how the implementation of the Counseling Guidance Program Service with the Case Handover Model at SMKN 1 Cijulang, Kondangjajar Village, Sub-district. Cijulang, Regency. Pangandaran. This study used a descriptive method with qualitative data. The results of the research show that the counseling guidance program service using the case transfer model was carried out because the student had a serious case. The school usually collaborates with more competent parties, for example psychologists or the police. For example, if a student is affected by a serious case that cannot be resolved with guidance and counseling, the school immediately transfers the case to a party with more expertise, such as Health if the student experiences a serious mental disorder and the Police if the student commits a crime. But so far, it is said that the students of SMKN 1 Cijulang have not had any counseling guidance on cases that have to go beyond the scope of the school to psychologists or the police.